A natureza dos padrões de variação espaço-temporal do volume veicular em ambiente urbano: estudo de caso em Fortaleza - Oliveira, Marcus Vinicius Teixeira de (2004)
The dynamic behavior of urban activities affects both temporal and spatial variability of traffic flow in urban road systems. Knowing this variability is essential to effectively control the urban traffic. In this sense, considering that the nature ofthe urban trips is an essential issue to traffic engineering, the knowledge of the traffic volume variation patterns is fundamental to the traffic planning, design, and operation. Therefore, this research intends to assess the spatial/temporalvariation trends of traffic volumes in a sample of urban arterial streets in Fortaleza, Brazil. The traffic volume data used in this study were obtained from the loop detectors network of the centralized adaptive traffic signals of the Fortalezaís Urban Traffic Control Center (CTAFOR). The analyses conducted in this research tried to associate the variation of traffic volume with peak hour, days of the week, and months of the year, as well as with the road functional classification and its operational and spatial aracteristics,seeking to identify cause-effect relationships. The author believes that this research contributes to the understanding of trends of the traffic volume in short and long terms, as well as to the identification of the typical conditions. Therefore, analyses were conducted to verify the effects of the temporal and spatial factors on the traffic volume, which is fundamental to support strategic and operational actions, as well as to help decision makers to better manage urban traffic.